Early repolarisation among athletes - Claessen, F. M. A. P.; Peeters, H. A. P.; Sorgdrager, B. J.; van Veldhoven, P. L. J. (Experimental Physiology, 2020)
Objectives Traditionally, early repolarisation (ER) is considered a benign ECG variant, predominantly found in youths and athletes. However, a limited number of studies have reported an association between ER and the incidental occurrence of ventricular fibrillation or sudden cardiac death. Yet definite, direct comparisons of the incidence of ER in unselected, contemporary populations in athletes as compared with non-athletes and across different sports are lacking. This study therefore aimed to investigate whether ER is more common among athletes as compared with non-athletes, and if ER patterns differ between sport disciplines based on static and dynamic intensity.